The Contradictions of Private Higher Education Expansion in India - Mathews, Eldho (International Higher Education, 2017)
When it comes to university-level education in India, a majority of students and parents prefer government and government-aided private institutions, as contrasted with the strong presence of private providers at the primary and secondary levels. This article explores the range of providers at the tertiary level.